An optimized graphene oxide self-assembly surface for significantly enhanced boiling heat transfer. (September 2019) - Zhou, Wenbin; Mao, Lan; Hu, Xuegong; He, Yu
Abstract: The enhancements in boiling heat transfer, i.e., critical heat flux (CHF) and heat transfer coefficient (HTC) can bring immediate benefits to improve the safety, efficiency and cost of heat energy transfer and conversion systems, leading to substantial global energy savings and reduction in greenhouse gas emissions. The enhanced boiling surfaces with great durability are highly desired for energy-intensive industrial applications. Here an optimized graphene oxide (GO) self-assembly surface for significantly enhanced boiling is developed, which could be readily fabricated utilizing the nucleate boiling self-assembly method. The optimal GO boiling surface produces remarkable improvements in boiling heat transfer performance (a CHF of 261 W cm -2 and a HTC of 9.1 W cm -2 K −1 ), which is among the highest values ever reported for pool boiling heat transfer on the planar enhanced surfaces. Additionally, it shows a good durability. The prominent performance can be attributed to the formation of interconnected and highly thermally conductive GO laminate film with moderate thickness on the substrate, which facilitates rapid cooling and rewetting of the local hot/dry regions, as well as bubble nucleation, thereby delay the occurrence of film boiling regime. The proposed strategy in current work is highly scalable and possesses enormous potentials in pragmatic applications. Graphical abstract: Image 105882